رائية ابن درَّاج القسطلي (ت421ه‍) دراسة سيميائية - جعفر عبد الحسين صادق (Journal of College of Education, 2019)
Ra’iyyah Ibn Daraj from the literature of the opposition, organized by the poet in the purpose of praising the Mansour bin Abi Amer, one of the kings of the sects and the forerunner: Invitation to the intimacy of the menstrual cycle. It is opposed to two previous poems, one of Abu Nawas and the other of al-Baghdadi. The semia- tical approach is based on a European approach to the study of signs and textual references, which de Saussure defines as "science studying the life of signs in the center of social life" And in the literature is a critical approach addressed to study the relations between the word and the meaning, and reading the letters reading semiotics (3) What carries the first form of the word, including color, name and address to the functions of time and space and others, and carries the connotation of distant hints drown in Deep The text reveals his relations with reality, and my work here is an attempt in this context, I hope to be a building block for high literature.